The importance of stem cells in the treatment of type 1 diabetes, type 2 diabetes and diabetes complications: The importance of stem cells in diabetology - Kamińska, Monika; Jasiewicz, Maria; Miernik-Skrzypczak, Magdalena; Spyra, Aleksandra; Malicka, Marta; Dąbrowska, Natalia; Kozioł, Aleksandra; Moczyróg, Katarzyna (Quality in Sport, 2025)
Introduction and Purpose. Diabetes, characterized by hyperglycemia due to impaired insulin production or action, leads to significant complications like diabetic retinopathy (DR) and diabetic foot syndrome (DFS). Current treatments manage symptoms but do not fully address disease progression. Stem cells, with their regenerative potential and immunomodulatory properties, represent a promising avenue for treating diabetes and its complications. This study explores the use of stem cell therapy in managing type 1 and type 2 diabetes, DR, and DFS. Material and Method. The study reviewed existing literature on the application of stem cells in diabetes treatment. More than 30 articles addressing these issues were analyzed. They were found using the PubMed search engine, and the time frame of these publications covered the last 20 years. Results. Stem cells demonstrated significant potential in diabetes management. For type 1 diabetes, MSCs reduced inflammation, preserved pancreatic islet function, and decreased insulin requirements without major adverse effects. Pluripotent stem cells showed promise in islet transplantation, achieving stable glycemic control in clinical trials. In type 2 diabetes, stem cell therapy improved insulin sensitivity and reduced insulin dependency, with evidence of β-cell regeneration. Complications like diabetic foot ulcers and retinopathy also responded positively to stem cell treatments. MSCs improved wound healing by enhancing tissue regeneration and reducing inflammation, while retinal therapies showed promise in slowing disease progression and repairing damaged vasculature. Conclusions. Stem cell therapies offer a promising approach for diabetes and its complications, particularly for regenerative applications in DR and DFS. While initial results are encouraging, further large-scale studies are needed to optimize protocols, assess long-term safety, and establish standardized clinical applications.